MEMBANGUN SUMBERDAYA PERIKANAN: PELUANG DAN TANTANGAN - Indah Susilowati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
Indonesia as an archipelago country has a great endeavor in fisheries and ocean resources. The strategy outlined by Indonesia in developing fisheries resource is by controlling the capture fisheries and extensification for inland fisheries. The code of conduct for responsible fisheries as stipulated by the global market should be fulfilled in all channels, such as production, processing, and distribution. Therefore, it is indeed need for all stakeholders to prepare and to anticipate any possibilities for the future market.